Introducing Kudu and Kudu architecture : understanding the big data storage manager that addresses the Hadoop storage gap problem - Bosshart, Ryan (O'Reilly Media, 2017)
"Apache Kudu is an entirely new storage manager for the Hadoop ecosystem. It addresses many of the most difficult architectural issues in Big Data, including the Hadoop "storage gap" problem common when building near real-time analytical applications. This vexing issue has prevented many applications from transitioning to Hadoop-based architectures. In this course, you'll learn why Kudu exists, when to use it, the key concepts of Kudu's design, and how it enables simple, real-time analytics without the need for separate batch and speed layers. Designed for developers, architects, and engineers with some limited experience using Hadoop ecosystem components like HDFS, Hive, Spark, or Impala, the course describes how to architect Kudu applications that are low-risk, fast, scalable, and reliable."--Resource description page.